The Strontium Isotopic Composition and Origin of Burial Cements in the Lincolnshire Limestone (Bajocian) of Central Lincolnshire, England - Emery,D; Dickson,JAD; Smalley,PC (2009)
Strontium isotopic composition (87Sr/86Sr) of two petrographically, chemically and isotopically (δ18O and (δ13C) distinct phases of burial calcites from the Lincolnshire Limestone are indistinguishable (0-70820 ± 26). The mean 87Sr/86Sr ratio of these phases is considerably more radiogenic than 87Sr/86Sr ratios of Bajocian marine waters (~ 0-70725). Neither Bajocian marine waters nor meteoric waters buffered by host marine carbonate in the Limestone could have precipitated the burial spars. Radiogenic strontium may have been contributed from K-feldspar dissolution and/or clay recrystallization, either within clastic portions of the Limestone itself, or from major clastic units adjacent to the Limestone. Alternatively, Palaeozoic marine waters or remobilized Palaeozoic marine carbonate and/or sulphate could have supplied the necessary radiogenic strontium.